The shifting sands of evidence: a socio-legal enquiry into the development of medical guidelines - Jansen, FJ (2017)
Medical guidelines on the same medical condition differ between England and the Netherlands. These guidelines are referred to as evidence-based because they are supposedly based on a systematic searching for and appraisal of medical studies to drive recommendations for appropriate care for specific clinical circumstances. This comparative study interrogates what causes these differences and similarities between guidelines and tries to uncover the mechanisms behind the development of medical practice guidelines. Four case studies, on lower back pain and on type 2 diabetes in both countries, are used to provide a detailed empirical account of the development of medical guidelines. Interviews with guideline developers are combined with a detailed analysis of available guideline documents. The overarching finding of this thesis is that medical evidence plays a more limited and nuanced role in guideline construction than might be expected and that guidelines are manifestations of professional (self-) regulation. Importantly, the research also finds that institutions shape guidelines in a multitude of ways. This study has endeavoured to add to a more nuanced understanding of evidence within the literature: conceptualising evidence as part of a process of a social and institutional construction. This construction is used within a collaborative and communicative process aimed at creating 'objective facts'. Contrary to existing scholarship, this thesis argues that evidence merely informs the understanding of members of guideline groups while a range of economic, cultural, institutional, and political factors, that together form cognitive frames, provide the driving force behind the development of guidelines. Institutional factors have shown to be essential elements in guideline development, influencing all aspects of development through institutional cultures of practice. This study concludes that calling guidelines evidence-based is an important rhetorical instrument, which helps to conceal and legitimize some of the normative choices that are inherent in guideline making.